Deposition and characterization of ZnO thin films on teflon substrates / Nur Sa’adah Muhamad Sauki - Muhamad Sauki, Nur Sa’adah (2013)
Although zinc oxide has been researched extensively for a wide variety of applications, studies on ZnO thin films deposition on polymer subsjtrates are rarely reported. On the other hand, migrations of electronic devices from silicon and glass substrates to wearable and flexible polymer are extensively progressing, thus there is a need to study extensively the deposition of ZnO on polymer substrates. In our work, exploration of deposition methods of ZnO on Teflon substrate has been investigated. The thin film depositions have been carried out by using three methods, which are solgel spin coating method, sol-gel dip coating method and RF magnetron sputtering method. The physical structures of the thin films were observed by using field emission scanning electron microscope (FESEM), and X-ray diffractometer (XRD) was used to investigate the crystallinity of the thin film. The electrical properties were examined using 2-point probe current-voltage (I-V) measurement, and the optical properties were studied by using UV-Vis-NIR spectrophotometer for transmittance and photoluminescence (PL) spectrometer to investigate the luminescence properties. Through the investigations, we found that the ZnO thin films deposited by sputtering method gave the best results compared to the sol-gel methods, suggesting that RF magnetron sputtering is the suitable method to deposit ZnO thin films on the Teflon substrate. Further investigation on the optimization of sputtering parameters has been done. From the characterization results, it was found that the ZnO thin films deposited at 200 W and 5 mTorr of sputtering pressure shows the best electrical properties. The deposited ZnO thin films at optimurp parameter show the highest conductivity, 4.41 x 10'2 Sm' 1 and lowest resistivity, 2.27 x 101 fim. This was supported by the crystalline quality of the films from the XRD results. The ZnO thin films deposited at the optimum parameters was tested for humidity and gas sensor applications using ammonia gas and humidity chamber. It was found that the thin film deposited in this work was more sensitive to ammonia gas compared to the humidity.